Validation of the other as shamer scale in Brazilian portuguese (B-OAS) for adolescents (Revista Contexto & Saúde, 2026)
Objective: Validate the Other as Shamer (OAS) scale in Brazilian adolescents. Methods: The cross-culturally adapted version for Brazil (B-OAS) was administered to 325 adolescents aged 12 to 18 from Northeast Brazil. Psychometric properties analyzed were internal consistency, temporal stability (intraclass correlation coefficient – ICC), convergent validity (Depression, Anxiety and Stress Scale - DASS-21), discriminant validity (sociodemographic variables), predictive validity (dental caries and occlusal aspects) and factorial validity (exploratory factor analysis – EFA and confirmatory factor analysis -CFA) (α = 5%). Results: The instrument exhibited excellent internal consistency (α = 0.91; ω = 0.91) and stability (ICC = 0.96). A significant positive correlation was found between B-OAS and DASS-21 scores (rs = 0.66). EFA suggested a single-factor solution (41.6% variance). No associations were found between B-OAS scores and the presence of dental caries or the need for orthodontic treatment (p = 0.55). Scores were significantly higher in female adolescents (p = 0.003) and those with a family income of up to the monthly minimum wage (p = 0.025). Conclusion: B-OAS had satisfactory psychometric properties for Brazilian adolescents and, despite not being associated with the oral problems analyzed, it can be reliably used for other situations related to external shame.
Keywords: Adolescent Behaviors; Oral Health; Questionnaires; Reproducibility of Results; Shame; Validation Study